Nordenskiöld's voyage round Asia and Europe. A popular account of the north-east passage of the "Vega," 1878-80. - Hovgaard, Andreas Peter, 1853-1910.; Brækstad, Hans Lien, 1845- tr. (London, S. Low, Marston, Searle & Rivington, 1882)
Mode of access: Internet.